The Effect of Think-Talk-Write Strategy in Writing Procedure Text - Nasution, Dewi Kesuma (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2023)
This study was concerned on the significant effect of the students’ ability in writing procedure text by using think talk write strategy. The research was conducted in quantitative research that used experimental group and control group. The population of this study was 60 students at SMP Sinar Husni Medan. In this study the sample was divided into two groups: the experimental group and the control group.  T-test was used as formula to analyze the data. The data were calculated by using t-test formula. The writer used T-test formula to analyze the data. The data were calculated by using t-test formula. The result of the analysis shows that t-observed (9,35) was higher than t-table (1,67) and the degree of freedom (df) 58. Therefore, the null hypothesis (Ho) is rejected the alternative hypothesis (Ha) is accepted. There was a significant effect of Think Talk Write (TTW) strategy in writing procedue text